Effects of a Paediatric Antimicrobial Stewardship Program on Antimicrobial Use and Quality of Prescriptions in Patients with Appendix-Related Intraabdominal Infections - Sílvia Simó; Eneritz Velasco-Arnaiz; María Ríos-Barnés; María Goretti López-Ramos; Manuel Monsonís; Mireia Urrea-Ayala; Iolanda Jordan; Ricard Casadevall-Llandrich; Daniel Ormazábal-Kirchner; Daniel Cuadras-Pallejà; Xavier Tarrado; Jordi Prat; et al. (MDPI AG, 2020)
The effectiveness of antimicrobial stewardship programs (ASP) in reducing antimicrobial use (AU) in children has been proved. Many interventions have been described suitable for different institution sizes, priorities, and patients, with surgical wards being one of the areas that may benefit the most. We aimed to describe the results on AU and length of stay (LOS) in a pre-post study during the three years before (2014-2016) and the three years after (2017-2019) implementation of an ASP based on postprescription review with feedback in children and adolescents admitted for appendix-related intraabdominal infections (AR-IAI) in a European Referral Paediatric University Hospital. In the postintervention period, the quality of prescriptions (QP) was also evaluated. Overall, 2021 AR-IAIs admissions were included. Global AU, measured both as days of therapy/100 patient days (DOT/100PD) and length of therapy (LOT), and global LOS remained unchanged in the postintervention period. Phlegmonous appendicitis LOS (p = 0.003) and LOT (p < 0.001) significantly decreased, but not those of other AR-IAI diagnoses. The use of piperacillin-tazobactam decreased by 96% (p = 0.044), with no rebound in the use of other Gram-negative broad-spectrum antimicrobials. A quasisignificant (p = 0.052) increase in QP was observed upon ASP implementation. Readmission and case fatality rates remained stable. ASP interventions were safe, and they reduced LOS and LOT of phlegmonous appendicitis and the use of selected broad-spectrum antimicrobials, while increasing QP in children with AR-IAI.